1996
DOI: 10.1111/j.1745-4573.1996.tb00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heating End‐point Temperature on Volatiles From Poultry Meat ‐ a Review

Abstract: During heating of muscle foods, numerous volatile flavor components are generated. Both the identity and quantity of these volatiles are influenced by cooking end‐point temperature (EPT) and post‐cooking storage. Methods for assessing flavor volatiles include sensory tests and gas chromatographic (GC) methods. Static headspace GC techniques either with a packed or capillary column have been used to determine the volatiles individually and they are simpler in operation compared to sensory tests. High correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…During heating, meat flavor precursors, including free amino acids, peptides, sugars, nucleotides, organic acids, and fatty acids react with each other or degrade to produce large quantities of volatiles and form the typical flavor of cooked meat. Ang and Liu (1996b) indicated that more than 50% of volatiles increased linearly or quadratically as the end-point temperature of meat increased. Most of those induced-volatiles are related to the degradation of meat components as temperature increased.…”
Section: Cla and Animal Performancementioning
confidence: 99%
“…During heating, meat flavor precursors, including free amino acids, peptides, sugars, nucleotides, organic acids, and fatty acids react with each other or degrade to produce large quantities of volatiles and form the typical flavor of cooked meat. Ang and Liu (1996b) indicated that more than 50% of volatiles increased linearly or quadratically as the end-point temperature of meat increased. Most of those induced-volatiles are related to the degradation of meat components as temperature increased.…”
Section: Cla and Animal Performancementioning
confidence: 99%